An investigation into full-ring radial-gap air-riding seals for aeroengines - Kumar, Shubham (2019)
This thesis focuses on a study carried out for modelling, designing and testing a full-ring radial-gap air-riding seal configuration for applications in a Gas Turbine Engine.